DEVELOPING STUDENTS’ INTERCULTURAL COMMUNICATIVE COMPETENCE THROUGH CULTURAL TEXT-BASED TEACHING - Permatasari, Indah; Andriyanti, Erna (Indonesian Journal of Applied Linguistics, 2021)
Teaching a foreign language needs to include its relevant culture as the context of the language use. However, studies indicate that many English lecturers in Indonesia have not integrated culture yet in their teaching materials, resulting in students’ low intercultural communicative competence (ICC). This three-cycle class action research was aimed to improve the ICC of first semester students majoring in metallurgy engineering through cultural text-based intercultural teaching. It was designed to overcome problems related to the limited opportunity for speaking practice and insufficient cultural contents in the English materials. Classroom observations and interviews with 22 students and the lecturer revealed that this cultural text-based intercultural teaching was practical to improve the students’ ICC. The integration of cultural texts in various forms: pictures, mind-maps, reading passages, and videos relevant to the subject field, enables the students to interact indirectly with the cultures of people from diverse communities. Answering questions and discussing language and cultural elements as well as the contents of the texts shapes their critical thinking. Their achievement in the role-play is the reflection of their improved ICC and shows their enhanced English skills.  Nevertheless, the students’ limited grammatical knowledge and lack of writing practice became constraints during their writing test. Further studies might investigate the solution for this problem, especially related to the effectiveness of this intercultural teaching in other subject areas.